2016
DOI: 10.1016/j.biocel.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of MITF by AKT affects its downstream targets and causes TP53-dependent cell senescence

Abstract: Microphthalmia-associated transcription factor (MITF) plays a crucial role in the melanogenesis and proliferation of melanocytes that is dependent on its abundance and modification. Here, we report that epidermal growth factor (EGF) induces senescence and cyclin-dependent kinase inhibitor 1A (CDKN1A) expression that is related to MITF. We found that MITF could bind TP53 to regulate CDKN1A. Furthermore, the interaction between MITF and TP53 is dependent on AKT activity. We found that AKT phosphorylates MITF at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…and AKT-mediated phosphorylation at S467/S565/S510 both promote cytosolic MiT/TFE retention and/or degradation (15,17,39,40). Though these previous studies focused on the role of AKT in phosphorylation and nuclear translocation of MiT/ TFE proteins, it is notable that we found both total and nuclear levels of MiT/TFEs to be proportionally affected by mTORC1 or AKT modulation.…”
Section: Micementioning
confidence: 51%
See 2 more Smart Citations
“…and AKT-mediated phosphorylation at S467/S565/S510 both promote cytosolic MiT/TFE retention and/or degradation (15,17,39,40). Though these previous studies focused on the role of AKT in phosphorylation and nuclear translocation of MiT/ TFE proteins, it is notable that we found both total and nuclear levels of MiT/TFEs to be proportionally affected by mTORC1 or AKT modulation.…”
Section: Micementioning
confidence: 51%
“…Similarly, genetic or longer-term pharmacologic mTORC1 inhibition decreased MiT levels and activity and lysosomal gene transcription. Yet these data are at odds with current models suggesting that mTORC1 suppression pro- S467/S565/S510 in TFEB, TFE3, and MITF, respectively, results in their cytoplasmic retention/inactivation (17,39) or proteasomal degradation (1,40). We conducted a TMT-based phosphoproteomic analysis of control and Rptor-KO keratinocytes, and found p-TFE3 (S564/565) levels to be significantly increased in Rptor-mary neurons showed increased autolysosome formation and autophagic flux via AMPK-dependent ULK1 activation, bypassing mTORC1-dependent ULK1 inhibition (38).…”
Section: Inhibition Of Hyperactive Akt In Mtorc1-inhibited Cells Rescmentioning
confidence: 83%
See 1 more Smart Citation
“…In recent studies, AKT also directly induced MITF phosphorylation at Ser510; p‐MITF is degraded by protease (Wang et al, ). This could explain why the PI3K inhibitor induced more melanin synthesis than the GSK3β inhibitor.…”
Section: Discussionmentioning
confidence: 93%
“…S3, where S409 in MITF-M corresponds to S516 in MITF-A) (Palmieri et al 2017). Using a phosphorylation mimetic "S510D" mutant, Wang et al (2016) reported that MITF was degraded more rapidly, suggesting that AKT promotes MITF degradation. This would be consistent with results from the Ploper et al (2015) study that reported that phosphorylation on S409 primes for phosphorylation by GSK3 at S405, S401, and S397, leading to destabilization of MITF AKT-mediated phosphorylation of MITF was also reported to stimulate MITF interaction with p53 and promote CDKN1A expression, while nonphosphorylated MITF was able to activate better tyrosinase expression .…”
Section: Mitf Posttranslational Regulationmentioning
confidence: 99%